A MSMEs PERCEPTIONS ON THE USE OF THE INDONESIAN QUICK RESPONSE CODE (QRIS) AS A TRANSACTION TOOL - Khoirurrizki, Kaila Zulfa (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to determine the perceptions of MSMEs on the use of QRIS as a transaction tool and the inhibiting factors experienced by MSMEs in using QRIS. QRIS can be a convenience for MSMEs as a transaction tool, especially for MSMEs in order to realize comprehensive financial inclusion. This research is field research using descriptive qualitative methods. The results of the Kauman Village MSMEs research have a positive public perception of QRIS (Quick Response Code Indonesian Standard) making it easier for MSMEs as an effective, fast and efficient payment/transaction tool. The inhibiting factors experienced by MSMEs in using QRIS are 1) MSMEs have concerns regarding data security and privacy 2) infrastructure problems, such as unstable internet connections. 3) Differences in technological accessibility MSMEs and consumers do not have smartphones that support QRIS 4) people's habits that still rely on cash.